The ‘Staying Calm’ programme : an evaluation of the impact of group work on children’s emotional resiliency, behaviour, anger control and social problem solving skills - Whyard, Claire (2010)
Staying Calm’ is a small group programme designed to promote emotional skills, anger control and social problem solving skills in children. This study outlines an evaluation of the programme completed with 48 Year 5 and 6 children in two schools within a large shire county in the Midlands. The study begins by examining previous research and literature relevant to children’s emotional and social skills. A range of concepts and interventions that influence children’s emotional literacy, regulation, competence and resilience are discussed and anger is used as an example of the ways in which regulation of a specific emotion can be understood and promoted within schools. A randomised controlled trial design is used to evaluate the effects of the programme upon measures of children’s emotional ‘resiliency’ (using the Resiliency Scales, Prince Embury, 2007), behaviour (using teacher versions of the Strengths and Difficulties Questionnaire, Goodman, 1997) and teachers’ and parents’ views of children’s anger control, social skills and problem solving (using questionnaires designed for the ‘Staying Calm’ programme, Clifford & Davies, 2009). Results from the study show that ‘Staying Calm’ had a statistically significant positive impact upon teachers’ perceptions of children’s overall behaviour difficulties, peer relationship problems and prosocial skills. Teacher ratings of conduct problems showed a significant improvement for the children who had not taken part in the intervention. There was no evidence of a statistically significant impact on children’s perceptions of their ‘resiliency’ skills or adults’ ratings of emotional symptoms, hyperactivity, anger control and social skills. The results are discussed in relation to the material presented in the Literature Review and are examined in relation to implications for future provision and research. The study concludes with critical reflections upon the researcher’s personal approach to the study and choice of methodology.